1996
DOI: 10.1097/00001888-199604000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of debt on U.S. medical school graduatesʼ preferences for family medicine, general internal medicine, and general pediatrics

Abstract: The authors assess the importance of educational debt in graduates' primary care specialty choices, and the variety of mechanisms through which debt may influence career decisions. Logistic regression models were used to identify significant predictors of the primary care specialty choices made by the 1991 and 1992 graduates of U.S. medical schools. These predictors were debt itself; other financial indicators; certain medical school characteristics; certain practice location plans; certain demographic factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 0 publications
1
54
0
Order By: Relevance
“…18 -20 Three studies reported multivariate analyses with at least one other control variable. Of these, 2 did not find that gender predicted choice of family medicine, 21,22 whereas the other found that being female …”
Section: Gendermentioning
confidence: 91%
See 2 more Smart Citations
“…18 -20 Three studies reported multivariate analyses with at least one other control variable. Of these, 2 did not find that gender predicted choice of family medicine, 21,22 whereas the other found that being female …”
Section: Gendermentioning
confidence: 91%
“…22,26 The data from these studies provide limited support for the belief that Hispanics are more likely to select family medicine.…”
Section: Ethnicitymentioning
confidence: 92%
See 1 more Smart Citation
“…Student debt may have a modest effect on career choice, but the effect is complex 41,56,57 and other factors seem to be at least as important. 10,20,37,41,58-62 Women, older students, and students from rural areas are more likely to choose primary care careers, 10,36,57,63 but admission strategies selecting for these features have not been tested and there is some evidence to doubt they would succeed.…”
Section: Commonly Discussed Solutions To the Adult Primary Care Physimentioning
confidence: 99%
“…[24][25][26][27] Information systems, electronic health records and patient internet portals are diffusing across medical practices and enabling the collection and linkage of data from a wide range of settings. 28,29 At the same time, medical education is in a time of transition with duty hour restrictions for residents, 30,31 a shift to ambulatory settings for both residency and medical student training, increasing concern about student debt burden, 32 and a focus on teaching practice competencies rather than medical knowledge. 33,34 This transition is occurring as the physician workforce also changes, with a growing proportion of women (30 % of practicing physicians and 52 % of medical students) 35 , slow shifts in racial and ethnic diversity (17 % of current medical students identify as a racial or ethnic minority), 35 and a growing focus on work life balance.…”
Section: Introductionmentioning
confidence: 99%